PENGARUH INDEKS GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN DI IICG DARI TAHUN 2007-2010 - Raissa Resti Fauzi; Kamaliah '; Al-azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study is aimed to determine the effect of the index of corporate governance on the company’s financial services from IICG in 2007-2010.The indicator Of index of corporate governance was measured with CGPI (Corporate Governance Perception Index) based on the report that released by IICG (Indonesian Institute for Corporate Governance) and the variable that used as indicators of financial services of the company were Return of Equity (ROE) and Return of Investment (ROI). The statistic method was used in hypothesis testing is simple regression with help of SPSS 20.00. The sample of this research were the companies that sequentially following the survey that held by IICG and already publish financial statement from 2007-2010.The result of this research showed that index of GCG influence ROE partially, but not ROI.Keywords : Index Good Corporate Governance (GCG), Return on Investment (ROI), Return on Equity (ROE.